169k views
2 votes
Simplify the following expression: (x + 6y) − (3x − 10y). If the final answer is written in the form Ax + By, what is the value of A (the coefficient in front of x)?

Write only the numeric value (no variables should be typed in your response).

User Tigris
by
4.3k points

2 Answers

3 votes

Answer: The values of A is -3

Explanation:

(x + 6y) − (3x − 10y)

distribute the negative to the second equation

x*-3x=-3x^2

x*10y=10xy

6y*-3x=-18xy

6y*10y=60y^2

take the end terms and create an equation

-3x^2+10xy-18xy+60y^2

combine like terms

-3x^2-8xy+60y^2~ final answer

-3 is the A term

-8 is the B term

60 is the C term

User Litbear
by
5.2k points
6 votes
X+6y-3x+10y =Ax +By
-2x +16y = Ax +By

A=-2
B=16
User Shahar Prish
by
5.1k points